1996
DOI: 10.1016/0304-8853(95)00730-x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction in double layered ME tapes

Abstract: A series of experimental double layered ME tapes with different oxygen concentrations were produced using an experimental mini-rollcoater setup. 6M measurements on these tapes indicate a negative (magnetostatic) interaction between the individual layers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…We attribute this to an aligning effect of the magnetisation direction in each layer caused by the stray field of the other layer. Immink et al [5] have also observed interactions between the layers of the same sample.…”
Section: Bilayer Mediamentioning
confidence: 95%
“…We attribute this to an aligning effect of the magnetisation direction in each layer caused by the stray field of the other layer. Immink et al [5] have also observed interactions between the layers of the same sample.…”
Section: Bilayer Mediamentioning
confidence: 95%
“…The multilayered structure was found to improve the magnetic properties, with an increase of the product M H c , and the recording performances, particularly at short recording wavelength. [2][3][4] In this work, the characteristics of the magnetic anisotropy in ME films, with two different compositions ͑Co-O and Co-Ni-O͒ and different numbers of layers, are studied. Because of the relatively complicated microstructure of the ME films, in which ferromagnetic grains with various sizes and shapes, Co-rich columns, and possible clusters of Co grains, coexist, the magnetic anisotropy field is not a single value and has a distribution.…”
Section: Introductionmentioning
confidence: 99%